Prospective association between milk intake and adiposity in preschool age children - Huh, Susanna Y (2010)
OBJECTIVE: To determine whether the quantity and type of milk (whole, 2%, or 1%/skim) consumed at age 2 is associated with adiposity at age 3. DESIGN: We assessed milk and dairy intake at age 2 with food frequency questionnaires completed by mothers. Our primary outcomes were body mass index (BMI) z-score and overweight at age 3 years, defined as BMI (kg/m(2)) for age and sex ≥ 85(th) percentile. SUBJECTS: 852 preschool-aged children in the prospective US cohort Project Viva. STATISTICAL ANALYSIS: We used linear and logistic regression models, adjusting for maternal BMI and education, paternal BMI, and child age, sex, race/ethnicity, intake of energy, non-dairy beverages, TV-viewing, and BMI z-score at age 2 years. RESULTS: At age 2 years, mean (SD) milk intake was 2.6 (1.2) servings per day. Higher intake of whole milk at age 2, but not low-fat milk, was associated with a slightly lower BMI z-score (−0.09 unit per daily serving [95% CI −0.16, −0.01]) at age 3; when restricted to children with a normal BMI (5(th) to < 85(th) %ile) at age 2, the association was null (−0.05 unit per daily serving [95%CI −0.13, 0.02]). Intake of milk at age 2, whether full or low-fat, was not associated with risk of incident overweight at age 3. Neither total milk nor total dairy intake at age 2 was associated with BMI z-score or incident overweight at age 3. CONCLUSION: Neither consuming more dairy products, nor switching from whole milk to low-fat milk at age 2, appears likely to prevent overweight in early childhood.